2019
DOI: 10.1080/23752696.2019.1642123
|View full text |Cite
|
Sign up to set email alerts
|

The exploration of students’ learning gain following immersive simulation – the impact of feedback

Abstract: With an increasing emphasis on the importance of real-world learning in higher education, coupled with demand for placement experience, simulation has become an increasingly popular pedagogy. However, literature is scant on how students feedforward their learning from the simulation debrief into placement. A mixed-method study of 108 student nurses explored how feedback from the debriefing contributed to students' learning from immersive simulation and whether students used this learning in the placement that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…To ascertain whether learning gain had been achieved, research using a mixed-methods approach was carried out (Morley, Bettles, & Derham, 2019). Students recognised the immersive simulation event as a valuable learning opportunity and considered it had informed their professional development and preparation for practice.…”
Section: Case Study 3 Real-time Immersive Simulation To Evaluate Studmentioning
confidence: 99%
“…To ascertain whether learning gain had been achieved, research using a mixed-methods approach was carried out (Morley, Bettles, & Derham, 2019). Students recognised the immersive simulation event as a valuable learning opportunity and considered it had informed their professional development and preparation for practice.…”
Section: Case Study 3 Real-time Immersive Simulation To Evaluate Studmentioning
confidence: 99%
“…To add on, in AfL practice, through questioning, teacher can adjust, modify the instruction to meet student learning goals. The adjustment and modification can be intentionally done in a meaning negotiation process or a feedback activity (Eckerth, 2009;Palma, 2014), from which teacher can gather information to potentially attain the leaning goals (Box et al, 2015;Carless, 2011;Clark, 2010;Deeley, Fischbacher-smith, Karadzhov, & Koristashevskaya, 2019;Gan, 2010;Hargreaves, 2005;Lee et al, 2015;Matthews, 2019;Mcclean & Hourigan, 2015;Morley, Bettles, & Derham, 2019;Walker, Salines, Abdillahi, Mason, & Molesworth, 2019) In this respect, teacher questions serve a guidance to both teacher and students to reflect their current stages in teaching-learning and subsequently are able to have a better further action as expected in AfL. Through questions, the AFL might be carried out in such a way that teacher, students, and peers have diagnostic information to decide a better further instruction (Huang & Hu, 2016;Lam, 2016;Lee, 2011;Obeiah & Bataineh, 2016).…”
Section: Afl and Questioningmentioning
confidence: 99%
“…Using Evan's theory of re-contextualisation, Morley, Bettles and Derham (2019) found that assumptions that certain pedagogies, such as simulation, naturally carried learning into the practice context were often incorrect. Multiple barriers, such as the students' confidence to admit to their learning needs with their new practice supervisor, were highlighted and demonstrated the importance that attention was given to theoretical connections and university learning in the different context of practice.…”
Section: Assessment 1 2000 W 35% Weighted Critical Analysis Essaymentioning
confidence: 99%